Optical design using excel: practical calculations for laser optical systems - Nakajima, Hiroshi (Wiley, 2015)
A practical introductory guide to optical design covering geometrical optics, simple wave-optics and diffraction, using Excel software• explains practical calculation methods for designing optical systems with fully worked-out examples and avoiding complex mathematical methods • includes practical calculations for ray tracing, laser beam (Gaussian beam) focusing, and diffraction calculations; the ray tracing and the diffraction calculations are done by using the VBA program which Excel provides as a supporting tool • describes basic optical theory and application methods, and provides readers with calculation methods for designing laser optical systems with numerous practical calculation examples. After finishing the book, even inexperienced readers should have the ability to design laser optical systems • covers large areas of geometrical optics and diffraction theory, providing a good overview and reference for beginners or non-specialist engineers • accompanied by a website including password protected electronic files